228k views
0 votes
What polynomial could you add to 3x^4-9x^3+5x^2-x+7 to get the sum of 3+4x^4+3x-x^3+3x^2?

1 Answer

6 votes

Answer:

Explanation:

to find what you need to add, ur gonna have to subtract.....subtract the second polynomial from the first one

but lets rearrange the second one

4x^4 - x^3 + 3x^2 + 3...thats better

now, we subract

3x^4 - 9x^3 + 5x^2 - x + 7 - (4x^4 - x^3 + 3x^2 + 3) =

3x^4 - 9x^3 + 5x^2 - x + 7 - 4x^4 + x^3 - 3x^2 - 3) =

-x^4 - 8x^3 + 2x^2 - x + 4 <=== ur answer

User Nathalee
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.